The Role of Virtual Reality in Enhancing the Quality of History Learning: A Systematic Literature Review Based on SDG 4 - Acim Acim; Muhammad Junaldi Jufri (Jurnal Pendidikan Progresif, 2026)
This study aims to analyze prior research on the application of Virtual Reality in history education and its role in improving educational quality. Furthermore, the analysis linked Virtual Reality's role to the objectives of SDG 4 (Quality Education). A systematic literature review (SLR) was conducted to filter relevant articles using the PRISMA guidelines. After screening, 20 articles that met the inclusion criteria were selected and then analyzed descriptively. The findings indicate that the use of Virtual Reality generally contributed to improving the quality of history learning across the 20 reviewed articles. However, variations were observed in effectiveness and implementation, influenced by the types of VR employed, including the Anne Frank VR House, 360° videos, HMD-based VR, Oculus Quest 2, CloudPano, and VR-based games. The potential of Virtual Reality (VR) to support several targets under SDG 4, particularly SDG 4.1 on improving the effectiveness of learning, SDG 4.3 on access to technology-based higher education, SDG 4.4 on the development of 21st-century digital skills, SDG 4.5 on inclusive and equitable education, and SDG 4.c on improving the competence of educators. This study finds that virtual reality has the potential to enhance the quality of history learning by enabling exploration of visual spaces. However, there are challenges in its implementation that require teacher training and support from schools and the government, as well as adequate funding and infrastructure, to maximize the use of Virtual Reality in history learning. Future research is expected to expand the scope of the database, the types of technologies, and the SDG aspects analyzed, yielding a more comprehensive understanding of the role of immersive technologies in sustainable education. Keywords: virtual reality, history learning, SDGs4, systematic literature review.